IDENTIFICATION OF INFLUENZA VIRUSES IN HUMAN AND POULTRY IN THE AREA OF LARANGAN WET MARKET SIDOARJO-EAST JAVA, INDONESIA - Frederika, Edith; Mareta, Aldise; Poetranto, Djoko; Wulandari, Laksmi; Setyoningrum, Retno Asih; Setyowati, Lucia Landia; Yudhawati, Resti; Soegiarto, Gatot; Yamaoka, Masaoki (Institute of Topical Disease Universitas Airlangga, 2013)
Background: Influenza is a viral infection that attacks the respiratory system (nose, throat, and lungs) that commonly known as